Maize endosperm texture characterisation using the rapid visco analyser (RVA), X-ray micro-computed tomography (μCT) and micro-near infrared (microNIR) spectroscopy - Guelpa, Anina (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD (Food Sc))--Stellenbosch University, 2015.